Language Policies as an Instrument of Shaping and Rhetoricizing Mutual Relations in the Post-Soviet Region - Hordecki, Bartosz (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2019)
The post-Soviet region is inhabited by communities using a high number of languages and dialects. This linguistic mosaic has been formed for millennia. Very often it turned out to be a factor seriously influencing the development of the geopolitical situation in this part of the globe. The post-Soviet region remains a space where language issues are still challenging and very sensitive. In large measure, traditional problems became more complicated during the period of the regional expansion of the Russian language in the nineteenth and twentieth centuries. Nowadays, states in the region try to create more or less autonomous language policies, sometimes calculated on relieving and sometimes on fueling socio-political conflicts. Language policies often turn out to be the instrument by which players in the region are trying to diminish or increase the gap in mutual relations. Additionally, political solutions applied to language issues often serve as a kind of argument in the axiological rivalry between communities living in the area of the former USSR. The paper aims to analyze some selected aspects of these policies. It also tries to characterize in general their rhetorical qualities and argumentative potential.

Obszar postradziecki zamieszkują wspólnoty posługujące się wielką liczbą języków i dialektów. Mozaika językowa regionu kształtowała się przez tysiąclecia. Częstokroć stanowiła czynnik poważnie oddziałujący na rozwój sytuacji geopolitycznej w tejże części globu. Obszar postradziecki pozostaje przestrzenią, w której kwestie językowe nadal jawią się jako wyzwanie. W sporym stopniu tradycyjne problemy uległy komplikacji w okresie regionalnej ekspansji ruszczyzny w wiekach XIX oraz XX. Aktualnie państwa regionu starają się prowadzić bardziej lub mniej autonomiczne polityki językowe, niekiedy obliczone na łagodzenie, niekiedy na zaostrzanie miejscowych konfliktów socjopolitycznych. Polityki te nierzadko okazują się instrumentem, przy pomocy którego gracze regionalni usiłują niwelować tudzież zwiększać rozdźwięki w stosunkach wzajemnych. Co więcej, rozwiązania polityczne w kwestiach językowych często służą jako argumenty w rywalizacji aksjologicznej pomiędzy wspólnotami zamieszkującymi przestrzeń byłego ZSRR. Celem tekstu jest analiza wybranych aspektów wspomnianych polityk. Stanowi on także próbę ogólnej charakterystyki ich właściwości retorycznych oraz potencjału argumentacyjnego.
Polityki językowe jako instrument kształtowania i retorycyzmu w stosunkach wzajemnych w regionie poradzieckim
Keywords: Language policy; rhetorical aspects of language policy; the Post-Soviet Region; the specificity of language policies in the Post-Soviet Region; polityka językowa; aspekty retoryczne polityki językowej; obszar postradziecki; specyfika polityk językowych obszaru postradzieckiego